Government guarantees and bank risk taking incentives - Markus Fischer; Christa Hainz; Jörg Rocholl; Sascha Steffen (European School of Management and Technology (ESMT), 2014)
This paper analyzes the effect of the removal of government guarantees on bank risk taking. We exploit the removal of guarantees for German Landesbanken which results in lower credit ratings, higher funding costs, and a loss in franchise value. This removal was announced in 2001, but Landesbanken were allowed to issue guaranteed bonds until 2005. We find that Landesbanken lend to riskier borrowers after 2001. This effect is most pronounced for Landesbanken with the highest expected decrease in franchise value. Landesbanken also significantly increased their off-balance sheet exposure to the global ABCP market. Our results provide implications for the debate on how to remove guarantees.
urn:nbn:de:101:1-201402136761
Keywords: G20; G21; G28; 650; Government guarantees; exits; risk taking; franchise value; financial crisis; loans